Research on electro-hydraulic composite drive winch and energy recovery system for mobile crane - Xu, Xianggen; Lin, Tianliang; Ren, Haoling; Guo, Tong; Li, Zhongshen; Miao, Cheng (Frontiers in Energy Research, 2023)
Due to the high power consumption and limited control precision of the traditional hydraulic drive winch system, the hydraulic and electric type energy recovery systems are proposed. The accumulator used in the hydraulic type has low energy density, which is difficult to store a large amount of energy. While the electric motor/generator used in the electric type cannot solve the secondary slip because of oil leakage, which leads to low controllability and high power consumption under near-zero speed and high torque conditions. Thus, based on electric construction machinery with high-pressure energy-density electric energy storage units, an electro-hydraulic composite drive winch and energy recovery system and control strategy for mobile cranes are proposed. Considering the good control characteristics of the electric motor/generator and the high power density of the hydraulic accumulator, a hydroelectric composite drive and energy recovery system are proposed to solve the secondary sliding and ensure the large torque output at near zero speed. A simulation model of the mobile crane is established to verify the feasibility of the proposed system and control strategy. The research results show that the system is more efficient at recovering energy when the weight is lowered by a greater distance.